حدود واجب طاعة الأوامر الرئاسية في قانون الوظيفة العامة 06/03 - بن ناصر, البشير (جامعة الوادي university el-oued, 2021)
واجب الطاعة الرئاسیة هو حجر الأساس في أداء المرفق العمومي لأعماله وبالتالي یحتل الصدارة والأولویة في واجبات الموظف العمومي كالتزام یقضي بامتثال وتنفیذ المرؤوس للأوامر الصادرة عن رؤسائه الإداریین، مع التزامه باللباقة والاحترام في التعامل معهم، كما أنه واجب یقوم على وجود رئیس ومرؤوس وأمر رئاسي، هذا الأخیر الذي یعتبر وسیلة التواصل بین طرفي الطاعة. أضف إلى أنه یمكن القول أن واجب الطاعة الرئاسیة العامل الرئیسي لاستمرار وحسن سیر المرافق العامة، الأمر الذي أثار جدلا فقهي كبیر بسبب امتداد نطاقه لیشمل الأوامر الرئاسیة غیر المشروعة، حمایة لاستقرار وسیرورة المرافق على حساب مبدأ المشروعیة، الأمر الذي اختلفت فیه النظریات الفقهیة والتي لم یظهر أن المشرع الجزائري استقر على أي منها. أما بالنسبة لإخلال المرؤوس بواجب الطاعة فإن ذلك لا یؤدي إلى قیام المسؤولیة التأدیبیة فقط، بل یمكن في ذات الوقت أن یؤدي إلى قیام المسؤولیة المدنیة و The duty of obeying superiors at work is the cornerstone of the well performance of the public service. Therefore, it constitutes the top priority in the duties of the public servant as a commitment to follow and execute the orders of his superiors, while being committed to respect and courtesy in dealing with them. It is also a duty based on the existence of a superior, a public servant and superior orders, this latter serves as a means of communication between the two. In addition, it can be said that the duty of presidential obedience is the main factor in the continuity and good functioning of public utilities, which sparked a great jurisprudential controversy due to its extension to include illegal presidential orders, to protect the stability and operation of facilities at the expense of the principle of legality, which differed in the jurisprudential theories that did not appear That the Algerian legislator settled on any of them. As for the violation of the subordinate to the duty of obedience, this leads not only to disciplinary responsibility, but also to civil and criminal liability. In the context of providing important guarantees to the duty-bearer to protect him from the consequences of his responsibility provided that what is required of him in implementation of the orders of his superiors. الجنائیة، كل ذلك في إطار تقدیم ضمانات هامة للموظف القائم بواجب الطاعة، تعصمه من آثار المسؤولیة التي تحیط به، شرط أن یكون ما بدر منه تنفیذا لأوامر رؤسائه الإداریین.
مذكرة ماستر